2022
DOI: 10.1088/1361-648x/ac9cc5
|View full text |Cite
|
Sign up to set email alerts
|

Magnus induced diode effect for skyrmions in channels with periodic potentials

Abstract: Using a particle based model, we investigate the skyrmion dynamical behavior in a channel where the upper wall contains divots of one depth and the lower wall contains divots of a different depth. Under an applied driving force, skyrmions in the channels move with a finite skyrmion Hall angle that deflects them toward the upper wall for $-x$ direction driving and the lower wall for $+x$ direction driving. When the upper divots have zero height, the skyrmions are deflected against the flat upper wall for $-x$ d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 56 publications
0
7
0
Order By: Relevance
“…Since fewer skyrmions are present in the sample after the annihilation is complete, and these skyrmions have shrunk in size due to the pressure from the applied current, the remaining skyrmions are able to pass more easily through the funnel opening and the net velocity along the easy flow direction is increased. In addition, the surviving skyrmions interact strongly with the wall and experience a Magnus velocity boost [29,56].…”
Section: Skyrmion Annihilationmentioning
confidence: 99%
“…Since fewer skyrmions are present in the sample after the annihilation is complete, and these skyrmions have shrunk in size due to the pressure from the applied current, the remaining skyrmions are able to pass more easily through the funnel opening and the net velocity along the easy flow direction is increased. In addition, the surviving skyrmions interact strongly with the wall and experience a Magnus velocity boost [29,56].…”
Section: Skyrmion Annihilationmentioning
confidence: 99%
“…89,90 . Additionally, diode-like effects have been investigated in channels with periodic potentials 91 and funnel-type geometries 92 . Numerous effects attributed to pinning defects on ferromagnetic skyrmions and other magnetic textures in one-and twodimensional systems is reviewed in the work of Ref.…”
Section: Skyrmion Dynamics In Tailored-design Racetracksmentioning
confidence: 99%
“…It is reported that a ratchet effect is a net direct current transmission generated by a combination of disrupted spatial symmetry and oscillatory drive, which can be understood by a skyrmion diode effect [25,26]. There are some suggestions on how to construct the ratchet geometry of skyrmions, such as by using asymmetric potentials, interfaces, etc [25,27].…”
Section: Introductionmentioning
confidence: 99%
“…It is reported that a ratchet effect is a net direct current transmission generated by a combination of disrupted spatial symmetry and oscillatory drive, which can be understood by a skyrmion diode effect [25,26]. There are some suggestions on how to construct the ratchet geometry of skyrmions, such as by using asymmetric potentials, interfaces, etc [25,27]. Up to now, the influence of voltage-controlled magnetic anisotropy (VCMA) on the motion of skyrmions [28][29][30][31] and its observations in experiments [32] have been investigated.…”
Section: Introductionmentioning
confidence: 99%